2009
DOI: 10.1055/s-0028-1088063
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Morita-Baylis-Hillman Acetates with Huisgen Zwitterions: A Novel Strategy for the Synthesis of β-Amino Acid Derivatives

Abstract: N o v e l S t r a t e g y f o r t h e S y n t h e s i s o f b -A m i n o A c i d D e r i v a t i v e sAbstract: The reaction of Huisgen Zwitterion with Morita-BaylisHillman acetates afforded b-amino acid derivatives.Although Huisgen zwitterion 1 was known for nearly four decades, its synthetic potential remained largely unexploited except in some notable reactions like Mitsunobu Reaction. 2 In view of our longstanding interest in zwitterion chemistry, 3 recently we have explored the reactivity of Huisgen zwitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
1
Order By: Relevance
“…An ortho substituent on the benzene ring of the MBH alcohol was also well tolerated (Table 2, entry 5 vs 6). Notably, in contrast with Nair’s report [24], it was revealed that aliphatic MBH alcohols were excellent candidates in the reaction. By switching the solvent to dichloromethane, several alkyl MBH alcohols containing ethyl, methyl, or hydrogen substituents ( 1h–l ) readily reacted with representative azodicarboxylates, producing the corresponding α-alkylidene-β-hydrazino esters 3 in high yields (80–90%) and good E / Z selectivity (Table 2, entries 9–18).…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…An ortho substituent on the benzene ring of the MBH alcohol was also well tolerated (Table 2, entry 5 vs 6). Notably, in contrast with Nair’s report [24], it was revealed that aliphatic MBH alcohols were excellent candidates in the reaction. By switching the solvent to dichloromethane, several alkyl MBH alcohols containing ethyl, methyl, or hydrogen substituents ( 1h–l ) readily reacted with representative azodicarboxylates, producing the corresponding α-alkylidene-β-hydrazino esters 3 in high yields (80–90%) and good E / Z selectivity (Table 2, entries 9–18).…”
Section: Resultscontrasting
confidence: 71%
“…In 2009, Nair and co-workers [24] reported an interesting reaction of MBH acetates with azodicarboxylates in the presence of PPh 3 (Mitsunobu reaction conditions), which gives an efficient access to α-alkylidene-β-hydrazino acid derivatives, an important precursor for many bioactive compounds [2530] including β-amino acids [25] (Scheme 1, top). However, the reaction exhibited poor chemoselectivity which gave comparable yields of tri- and tetrasubstituted hydrazines.…”
Section: Introductionmentioning
confidence: 99%